Dukungan Keluarga Terhadap Kemandirian Sosial Anak Tunagrahita - Ira Werni; Zulmiyetri Zulmiyetri (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
iTheproblems in this studymis the low social attention of parents towards the independence of mentally retarded children. The purpose of this research is to see how the relationship between social support of parents and the social independence of mentally retarded children. This research uses a descriptive-quantitative method. The population of this study were students and their parents at SLB Negeri 1 Bukittinggi. Withdrawal of research samples using total sampling, with the number of samples in this study 16 people. The test instrument in this study was a questionnaire using a Likert scale. With amsignificant level of 0.05. The results in this study found that parents' social support was in the Agree category with a percentage (38%). While the results of the percentage of social independence of mentally retarded children are in the Agree category with a percentage (44%). These results indicate that parents' social support is very necessary for the social independences of mentally retarded children. Parents' social support is very necessary in the social independence of mentally retarded children. Parental support will support the social independence of mentally retarded children. This is to support how mentally retarded children can carry out general activities independently, such as wearing their own clothes, eating alone, being able to tie their own shoelaces.